Degradation of Anti-Nutritional Factors in Maize Gluten Feed by Fermentation with Bacillus subtilis: A Focused Study on Optimizing Fermentation Conditions - Xiaohong Sun; Lei Ma; Yaoquan Xuan; Jianfen Liang (Fermentation)
Maize gluten feed is rich in micronutrients and serves as a good source of protein and dietary fiber, but also contains anti-nutritional factors. In this study, fermentation conditions for the degradation of phytic acid and water-unextractable arabinoxylans in maize gluten feed using Bacillus subtilis were optimized. Key variables influencing the fermentation process were identified from seven potential parameters using the Plackett–Burman design. Three statistically significant factors, i.e., fermentation time, inoculum dose, and material-to-liquid ratio were further optimized through a central composite design and the efficiency of fermentation conditions was predicted. The accuracy of the predicted model was validated by subsequent experimentation. The optimum fermentation conditions were determined to be a fermentation time of 84.5 h, inoculum dose of 17.1%, and material-to-liquid ratio of 1:3.4. Under these conditions, 48% of phytic acid and 32% water-unextractable arabinoxylans were degraded. Following fermentation, the activities of protease, xylanase, phytase, and cellulase in maize gluten feed were significantly increased (p < 0.001), contributing to the breakdown of phytic acid and water-unextractable arabinoxylans, which improved the protein dispersibility index, in vitro protein digestibility, and mineral bioavailability. These findings suggest that fermenting maize gluten feed with Bacillus subtilis is a practical and effective approach to reducing anti-nutrients and enhancing its nutritional quality.